Good Corporate Governance Mechanisms on National Banking Performance - Sarpinah, Dewi; Juliardi, Dodik; Utami, Helianti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The banking sector plays a crucial role in Indonesia's national economy because it functions as a financial intermediary institution that collects funds from the public and distributes them in the form of credit for productive activities. In the banking sector, the implementation of GCG is not merely a formality; it is the basis for risk management, strategic decision-making, and the protection of the rights of authorized parties, including creditors, shareholders, and depositors. This study aims to examine the effect of Good Corporate Governance (GCG) mechanisms on the financial performance of national banks listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The research method uses a quantitative explanatory approach. The population consisted of 47 banks, with a sample of 23 banks selected through a purposive sampling technique. The data were analyzed using multiple linear regression to test the influence of the variables of the Board of Commissioners, Audit Committee, Institutional Ownership, and Managerial Ownership on Return on Assets (ROA). The results showed that simultaneously, GCG mechanisms significantly influenced banking performance with an F value of 4.608 (Sig. 0.010). Partially, the Board of Commissioners, Audit Committee, and Managerial Ownership have a positive and significant influence on ROA. However, Institutional Ownership did not significantly influence financial performance. The coefficient of determination indicates that GCG mechanisms explain 50.6% of the variation in ROA, with the remainder influenced by factors outside the model. This study concludes that strengthening the supervisory function and aligning management interests are key to improving banking performance post-pandemic.